PENGUKURAN KUALITAS WEBSITE PENJUALAN TIKET DENGAN MENGGUNAKAN METODE MCCALL - Hanes Hanes; Angela Angela; Salsalina Br Sembiring (JTIK (Jurnal Teknik Informatika Kaputama), 2020)
Ticket reservations through agents or ticket sales points are very conventional. The web is the choice media to sell tickets for now. Customers can easily buy tickets like transportation ticket, events, and playground tickets through the web. Problems faced by some web users are the lack of responsiveness of the web, unstable connections, difficult usage, and the possibility of payment failure when transaction is done. Therefore, it is necessary to measure software quality using the McCall method. From the measurement results, web ticket sales get 80.56% which means the quality of the ticket sales web is good. Although the overall result is considered good, but ticket sales service providers must continue to improve the quality of the web.